Challenging communication in doctor / non-native patient encounters. Two perspectives, three types of interaction and some proposals - Valero-Garcés, Carmen (The Journal of Specialised Translation, 2010)
The progression toward multicultural societies, motivated in part by the rapid increase in migration over a short period of time, is having a noticeable impact on the quality of communication between professionals and their clients. This paper focuses on the analysis of communication in a specific setting, the Spanish healthcare system, from two different perspectives; that of the medic and that of the language specialist (the interpreter). Firstly, the importance given to language and its barriers as seen from both perspectives will be analysed; secondly evaluate the effectiveness of communication in medical contexts will be evaluated through the examination of the different modes of communication found in doctor / non-native patient interaction using a discourse-analytical approach; finally some conclusions about the quality of communication will be presented, together with some suggestions as to the best way of incorporating the results of this research into seminars for healthcare professionals and training programs for future interpreters. The results are not different from those of other studies, but we think that they serve as an illustration of reality and, using them as a starting point, we have an opportunity to improve communication in specific medical contexts, by combining theory, research and practice.